Metrology in digital production: VDI Status Report January 2023 - VDI / VDE (Verein Deutscher Ingenieure e.V., 2023)
Executive Summary This is the translation of the publication „VDI-Statusreport Fertigungsmesstechnik in der digitalen Produktion, 2021-11 [VDI/VDE GMA 2021], original in German language. Objective The aim of this document is to make the processes and structures for digitised integration of measurement technology into production transparent. For this purpose, the existing processes and structures as well as the software interfaces used, and the underlying models are presented. Based on this presentation, generally usable models for the digital representation of measuring systems and measurement orders in production are developed. The partially executed details of these models are to be understood as exemplary explanations. They will differ depending on the application and environment. Content Although digitalisation in its original meaning (analogue-digital conversion) has long played a leading role in measurement technology, paradigms such as Industry 4.0 require a comprehensive consideration of all aspects of measurement technology with regard to the digital acquisition, processing, distribution and representation of ...